2022
DOI: 10.1186/s13321-022-00671-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the structure-odor relationship using a Transformer model

Abstract: The relationships between molecular structures and their properties are subtle and complex, and the properties of odor are no exception. Molecules with similar structures, such as a molecule and its optical isomer, may have completely different odors, whereas molecules with completely distinct structures may have similar odors. Many works have attempted to explain the molecular structure-odor relationship from chemical and data-driven perspectives. The Transformer model is widely used in natural language proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…To obtain non-transfer features, we use state-of-the-art by zheng 53 . We train the SMILEStransformer 53 from scratch using our perceptual training data. To evaluate whether the model's performance is limited by the amount of data, we conduct training on progressively larger volumes of data from 20% to 80% of the whole dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain non-transfer features, we use state-of-the-art by zheng 53 . We train the SMILEStransformer 53 from scratch using our perceptual training data. To evaluate whether the model's performance is limited by the amount of data, we conduct training on progressively larger volumes of data from 20% to 80% of the whole dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5a shows the performance comparison between perceptual features learned with and without using a pre-trained SMILES-transformer model. To obtain non-transfer features, we use state-of-the-art by zheng 53 . We train the SMILEStransformer 53 from scratch using our perceptual training data.…”
Section: Resultsmentioning
confidence: 99%
“…‘Woody’ odorants are associated with rigid bulky hydrocarbon skeletons [ 23 ]. Whereas a subgroup discovery algorithm revealed the rule that ‘woody’ molecules are hydrophobic and rather not cyclic nor aromatic [ 24 ], investigations using a Transformer model suggested that woody molecules are often ring structures [ 26 ]. This is in accordance with our results, where cyclohexane structures were assigned the second highest influence values whereas aromatic structures scored low.…”
Section: Resultsmentioning
confidence: 99%
“…Though many advances in odor prediction have been achieved in recent years [ 10 – 20 ], we unfortunately still know little about the relationship between a molecule’s structure and its odor [ 21 23 ] to an extent where we can provide chemists with a toolbox for designing molecular structures with a specific odor in mind. However, sophisticated computational methods have led to new insights into these relationships [ 24 26 ] and allow prediction whether a molecule is odorous at all [ 27 ]. Adding to the hurdles in the field, there is dispute over the dimensionality of the odor space [ 7 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the results of machine learning, the study will further explore the chemical structure and mechanism of action of green odor molecules, revealing the potential laws of their functioning. Additionally, by using an internet service that is freely available to everyone, the binary classifiers developed through the application of machine learning can be employed, saving time and money [ 12 , 13 , 14 , 15 , 16 , 17 ]. This study presents a new breakthrough in the field of green odor research by applying machine learning for the first time to green odor molecular prediction.…”
Section: Introductionmentioning
confidence: 99%